RECONCILING INDUSTRIAL CLUSTERS AND URBAN SYSTEMS THROUGH REGIONAL NETWORK GOVERNANCE: A CASE OF CENTRAL JAVA PROVINCE - Prihadi Nugroho (Faculty of Economics and Business, Universitas Gadjah Mada, 2010)
The location distribution of industrial clusters is often associated with their proximity to production factors geographically and economically. Many studies show how industrial clusters can maximise inter-firm social and economic benefits through a process of collective efficiency and flexible specialisation. Particularly this condition can be achieved with a support of well-articulated urban systems where the integration of public service provisions can be established to reduce total transactional costs. In fact, most regions in Indonesia fail to present appropriate urban systems for ensuring the delivery of resources across regions. Moreover, the practices of decentralised developments since the past few years have been neglecting the importance of strengthened urban system following the tendency of governments to look after local developments. As a result, the industrial clustering approach which is implemented by some local governments only creates institutional obstacles and additional costs due to the lack of intergovernmental cooperation. Regarding this issue a regional network governance should be encouraged to provide coordination milieu between governments in developing industrial clusters altogether. This attempts may be useful to cutting off the regional differences of transactional costs that the respective clusters must cope with.Keywords: industrial clusters, urban systems, regional network governance